Molecular genetic control of leaf lifespan in plants - A review - Reza Shirzadian Khorramabad (Journal of Plant Molecular Breeding, 2013)
Leaf senescence constitutes the last stage of leaf development in plants and proceeds through a highly regulated program in order to redistribution of micro- and macro-nutrients from the senescing leaves to the developing/growing plant organs. Initiation and progression of leaf senescence is accompanied by massive sequential alterations at various levels of leaf biology including leaf morphology and physiology, cell metabolism and structure, and gene transcription. In this regard, comprehensive expression analysis of senescence-associated genes (SAGs) and the identification of leaf senescence related mutants has revealed that leaf senescence is a complex genetically controlled program. In this review, we present important findings about the molecular genetic mechanisms underlying leaf senescence in various plants with a main focus on the model plant Arabidopsis thaliana. Functional analysis of leaf senescence mutants has provided new insights into the key processes that regulate the onset and progression of leaf senescence, thus allowing categorization of the various regulatory factors into several signalling pathways.